Análise comparativa de genes das caseínas de búfalo - Naressi, Bruna Cristina Machado [UNESP] (2015)
Among milk proteins, the caseins (alpha-s1, alpha-s2, beta- and kappa-casein) play a crucial role considering their high nutritional value and physicochemical characteristics which contribute to the manufacture of dairy products. These proteins are encoded by the CSN1S1, CSN1S2, CSN2 and CSN3 genes, respectively. In order to analyze the buffalo casein genes and compare the sequences with other species, the goal of the present study was to identify, characterize and sequence clones from a buffalo genomic library. A total of 33,792 clones were evaluated, and two clones were identified as positive, one for the CSN1S1 gene (clone A/2) and other for the CSN3 gene (clone L/8). The DNA sequence from clone A/2 identified the whole CSN1S1 and a partial sequence from the CSN2 genes. The DNA sequence from clone L/8 revealed a partial sequence from the CSN3 gene. The CSN1S1 gene presented a total of 17,008 bp organized in 19 exons ranging from 24 bp to 380 bp and 18 introns ranging from 90 bp to 1,710 bp. Comparative analysis showed sequence conservation higher than 85% on exons and introns of the CSN1S1 gene when compared with the cattle gene sequence. The partial sequence from the CSN2 gene included exon 9 and part of intron 8, with conservation higher than 98% when compared with the cattle sequence. The partial sequences of the CSN3 gene included parts of the introns 2 and 3, the whole sequence of intron 4 and exons 3, 4 and 5. These sequences showed conservation higher than 94% with cattle. The identification of repetitive sequences showed that 43.83% of DNA sequence from clone A/2 and 44,98% from clone L/8 were represented by retrotransposable elements. Further comparative analysis showed buffalo specific repetitive sequences in the CSN1S1 gene and the partial CSN3 gene with when compared with other bovids species. The coding sequence of the buffalo CSN1S1 gene showed 98%, 93%, and 90% of identity with the correspondent sequences in cattle ...